Complications with PMMA compared with other materials used in cranioplasty: a systematic review and meta-analysis - Leão, Rafaella de Souza; Maior, Juliana Raposo Souto; Lemos, Cleidiel Aparecido de Araújo; Vasconcelos, Belmiro Cavalcanti do Egito [UNESP]; Montes, Marcos Antônio Japiassú Resende; Pellizzer, Eduardo Piza; Moraes, Sandra Lúcia Dantas (FapUNIFESP (SciELO), 2018)
Polymethyl methacrylate (PMMA) has been considered a suitable material for cranioplasty. However, no consensus has been reached concerning the best material for cranioplasty with regard to minimizing complications. Thus, this systematic review and meta-analysis aimed to compare the complication rates of PMMA with those of autologous bone and titanium mesh. This review was registered with PROSPERO (CRD42016042725). Systematic searches were conducted on PubMed/MEDLINE, Scopus, and Web of Science. The focus question was, Do PMMA prostheses used in cranioplasty have complications rates similar to those of autologous bone and titanium mesh? A meta-analysis of complication rates was performed on the basis of dichotomous outcomes assessed by risk ratio (RR) with corresponding 95% confidence intervals (CI). From 1014 data sources, 11 articles were selected according to eligibility criteria. These articles involved 1,256 individuals and 1,278 cranioplasties using autologous bone (n = 408), PMMA (n = 379), or titanium (n = 151). The follow-up period ranged from 63 days to 54.3 months. No difference was observed between the complication rates of PMMA and autologous bone (p = 0.94; RR, 0.98; 95%CI, 0.54-1.75) or between PMMA and titanium (p = 0.38; RR, 1.59; 95%CI, 0.57-4.48). Sub-analysis of the reasons for craniotomy (trauma/non-trauma) was conducted, which revealed no significant difference (p = 0.91; RR, 0.95; 95%CI, 0.37-2.42). The meta-analysis indicated that the use of PMMA yields complication rates that are near those of autologous bone and titanium mesh.